What we talk about when we speak of a quality artistic education: the Chilean case - Leonardo Verde Charréu; Madalena Campos Ghira (Revista Gearte, 2018)
Developed from a research work for a master's degree in artistic education taught at the Superior School of Education of the Polytechnic Institute of Lisbon, Portugal, the present work seeks to evaluate a publication in support of the National Plan of Arts Education that is being developed in current Chilean educational reform. Used as "classroom material", the analysed notebook has the axes that structure an educational intentionality that seems to us quite pertinent and deserving of study and prominence. As many of the problems of contemporary art education, in particular the lack of clear educational intentions, seem to be transversal to many countries, the work developed in Chile can be a reference not only to justify the presence of arts in the school curriculum, but also for the definition of an educational strategy that considers the improvement of the quality of life of the people as the priority objective to be achieved.